PENGGUNAAN EJAAN DALAM PERUMUSAN PERATURAN DAERAH NUSA TENGGARA BARAT The Use of Spelling in West Nusa Tenggara Rules Pattern - Kasman, Kasman (Jurnal Lingko : Jurnal Kebahasaan dan Kesastraan, 2020)
AbstrakBahasa Indonesia adalah bahasa negara dan bahasa persatuan. Munculnya varian baru yang mengancam kelestarian bahasa Indonesia menjadi alasan dilakukannya penelitian ini. Dengan demikian, penelitian ini bertujuan untuk mendeskripsikan bentuk-bentuk kesalahan ejaan dalam Perumusan Peraturan Daerah Nusa Tenggara Barat. Metode pengumpulan data yang digunakan dalam penelitian ini adalah metode pustaka sedangkan metode analisis data yang digunakan adalah metode komparatif. Hasil analisis data menunjukkan bahwa kesalahan ejaan yang terdapat dalam perumusan Peraturan Daerah Nusa Tenggara Barat digolongkan ke dalam tiga jenis, yakni: (1) kesalahan penggunaan huruf kapital; (2) kesalahan penggunaan tanda koma; dan (3) kesalahan penggunaan tanda titik dua.Kata-kata kunci: bahasa Indonesia, ragam hukum, kesalahan, ejaan, kapital, dan tanda bacaÂ AbstractIndonesian language is official state language and the language of national unity. Theemergence of a new variant that threatens the preservation of Indonesian is the reason for this research. One of the varieties that threatens the maintenance of Indonesian grammatical rules is legal language style. To see how it is different from other varieties, researcher tries to do a research on Indonesian grammatical rule, especially spelling used in legal style. Data source is West Nusa Tenggara Rules Pattern on the Development and Protection of Local Languages and Local Literatures and therefore, the purpose of the study is describe the spelling errors found the rules pattern. Method used to collect data is library method. While analysis method used is comparative method. Result of the analysis shows that there are three spelling errors found in West Nusa Tenggara Rules Pattern on the Development and Protection of Local Languages and Local Literatures. The three errors are (1) capitalization and (2) punctuation, covered comma, and (3) colon.Keywords: Indonesian language, legal style, errors, spelling, capitalization and punctuation.